Size and shape affects the antimicrobial activity of quaternized nanoparticles. Issue 3 (18th October 2018) - Inam, Maria; Foster, Jeffrey C.; Gao, Jingyi; Hong, Yuanxiu; Du, Jianzhong; Dove, Andrew P.; O'Reilly, Rachel K.
Abstract : Crystallization driven self‐assembly (CDSA) was utilized to prepare quaternized nanoparticles with spherical or platelet morphologies of different sizes to explore the effect of size and shape on their antibacterial activity. Small 2D platelets (< 1 µm) exhibited greater antibacterial activity than larger 2D platelets (ca. 4 µm), their corresponding spherical constructs, and unassembled polymer chains. This activity was dependent on the size, shape, and cell membrane structure of the bacteria.